Moda e inovação social : estudo de caso em uma comunidade criativa - Senandes, Joanna Carolo (2021)
Sustainability in fashion and design has grown due to environmental and social issues related to production and consumption processes in fashion. Clothing items have become cheaper and more accessible, in turn the fashion cycle is getting shorter and consumers often discard clothes after wearing it a few times. One of the concepts that arises from the need to answer question is of social needs and inequalities is that of social innovation. Considering this context and outlining the representativeness of the fashion universe in consumption, this study aimed to analyze how social innovation initiatives in a fashion ecosystem can contribute to the promotion of social innovation considering contextual aspects - micro and macro, economic and social integrated with sustainable fashion design, considering a sustainable fashion ecosystem located in a creative community called Vila Flores, located in the 4th district, in the city of Porto Alegre, RS. A qualitative research was carried out to better understand the problem, following this approach, in terms of objectives, exploratory research was used as a method, as it seeks a better understanding of the phenomenon and descriptive research, which aims to reach an explanation for the research. For data collection, 12 interviews were conducted with the actors that make up the Sustainable Fashion Ecosystem of RS, located in the creative community Vila Flores. The analysis considered dimensions of social innovation (with a focus on the transformations dimension), combined with a fashion kit with a focus on social and environmental aspects relevant to this universe. The results of the research show that initiatives in this fashion ecosystem promote social innovation, through the generation of income, social well-being and quality of life of the people benefited by the activities developed. The research contributions relate to the case study of a fashion ecosystem through the lens of social innovation, considering the motivating context of economic and social changes. The studied fashion ecosystem integrates social innovation initiatives with design in a successful way, its research is contributory from an academic point of view and practical due to the proposed analytical contribution.